2021
DOI: 10.3390/agronomy11061174
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Biochar Made from Agricultural Residues to Increase Soil Fertility and Microbial Activity: Impacts on Soils with Varying Sand Content

Abstract: Different types of soil respond variably to biochar amendment. Soil structure and fertility are properties which strongly affect the impacts of biochar on soil fertility and microbial activity. A pot experiment with lettuce was conducted to verify whether biochar amendment is more beneficial in sandy soil than in clay soil. The nutrient content (carbon and nitrogen), microbial biomass carbon, soil respiration, metabolic quotient, and plant biomass yield were determined. The treatments were prepared by mixing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(79 citation statements)
references
References 43 publications
1
78
0
Order By: Relevance
“…Soils with lower fertility are likely to experience a higher frequency of fluctuations in the active soil microbial biomass due to lower labile C and/or available nutrients when perturbed. Our results are in line with those of [ 41 ], suggesting that biochar amendment led to higher microbial biomass response in sandy soil than in clay soil. Zhang et al [ 42 ] also found that bacterial communities in soils with lower pH values (<7) experienced significant changes but not in alkaline soils pH (>7) following the application of biochar produced from peanut shells.…”
Section: Resultssupporting
confidence: 92%
“…Soils with lower fertility are likely to experience a higher frequency of fluctuations in the active soil microbial biomass due to lower labile C and/or available nutrients when perturbed. Our results are in line with those of [ 41 ], suggesting that biochar amendment led to higher microbial biomass response in sandy soil than in clay soil. Zhang et al [ 42 ] also found that bacterial communities in soils with lower pH values (<7) experienced significant changes but not in alkaline soils pH (>7) following the application of biochar produced from peanut shells.…”
Section: Resultssupporting
confidence: 92%
“…Carbon enriched-manures were prepared by two methods (a) by mixing of fresh manure with HA-rich product Humac AGRO (commercial soil fertility stimulator, mined from leonardite-oxihumolite, provided by Envi Produkt Ltd., Prague, Czech Republic), and (b) by mixing of fresh manure with biochar produced from agricultural waste (cereal husks, sunflower peels and fruit processing waste) at 600 °C (Sonnenerde GmbH, Riedlingsdorf, Austria). Detailed information on the amendment has been previously published [28,29].…”
Section: Procurement and Preparation Of C-enriched Manuresmentioning
confidence: 99%
“…The soil was collected from the experimental field near the town Troubsko, Czech Republic (49°10′28"N 16°29′32"E). The soil was silty clay loam (according to USDA Textural Triangle), Haplic Luvisol (according to WRB soil classification), properties are described in detail by Brtnicky et al [29]. The topsoil was dug up to the depth of 15 cm, big parts (stones, plants residues) were removed on a 2 mm sieve, the sieved soil was then thoroughly mixed with a fine quartz sand (0.1-1.0 mm) in a weight ratio of 1:1.…”
Section: Collection Of Soil Treatment Plan and Pot Experimentsmentioning
confidence: 99%
“…The content of nutrients in the topsoil used was as follows: total carbon (TC) 7.0 g·kg −1 , total nitrogen (TN) 800 mg·kg −1 , available phosphorus (P) 485 mg·kg −1 , and available potassium (K) 0.115 mg·kg −1 . The detailed properties of the soil used can be found elsewhere ( Holatko et al., 2020 ; Brtnicky et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The content of nutrients in the topsoil used was as follows: total carbon (TC) 7.0 g•kg −1 , total nitrogen (TN) 800 mg•kg −1 , available phosphorus (P) 485 mg•kg −1 , and available potassium (K) 0.115 mg•kg −1 . The detailed properties of the soil used can be found elsewhere (Holatko et al, 2020;Brtnicky et al, 2021). The control variant was unamended, whereas digestates were applied to the other variants at a dose corresponding to 40 t•ha -1 ; see Table 2.…”
Section: Pot Experimentsmentioning
confidence: 99%